Isonymic Relations in the Bolivia-Argentina Border Region - Dipierri, Jorge Edgardo (2017)
When migrating, people carry their cultural and genetic history, changing both, the transmitting and the recipient populations. This phenomenon changes the structure of the population of a country. The question is how to analyze the impact on the border region. A demographic and geopolitical analysis of borders requires an interdisciplinary approach. An isonymic analysis can be a useful tool. Surnames are part of cultural history, socio-cultural features transmitted from ancestors to their descendants through a vertical mechanism similar to that of genetic inheritance. The analysis of surname distribution can give quantitative information about the genetic structure of populations. The isonymic relations between border communities in southernBoliviaand northernArgentinawere analyzed from electoral registers. This comprised 89 sections included in 4 major administrative divisions, 2 from each country, which includes the international frontier. The Euclidean and geographic distance matrices where estimated for all possible pair wise comparisons between sections. The average isonymic distance was lower between Argentine than between Bolivian populations. Argentine sections formed three clusters, of which only one included a Bolivian section. The remaining clusters were exclusively formed by sections fromBolivia. The isonymic distance was greater along the border. Regardless of the intense human mobility in the past as in the present, and the presence of three major trans-border conurbations, the Bolivian-Argentine international boundary functions as a geographical and administrative barrier that affects differentially the distribution and frequency of surnames. The observed pattern could possibly be a continuity of pre-Columbian regional organization.